Peran Kepercayaan dalam Memediasi Pengaruh Keadilan Pajak terhadap Kepatuhan Wajib Pajak - Natalis Sinulingga (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to determine the role of trust in mediating the impact of tax justice on taxpayer compliance in Jakarta. Accidental sampling is the method used to get 100 respondents. Data collection was done by using a questionnaire. The technique used is data analysis with mediating variable regression. Based on the results of the analysis, it can be seen that the role of trust in communicating tax justice has a positive effect on taxpayer compliance.